Building a collaborative research community of practice and supporting research engagement in speech-language pathology: identification of stakeholder priorities. Issue 4 (9th December 2020) - McCurtin, Arlene; O'Connor, Anne; ,
ABSTRACT: Background and aims: Clinician engagement in research has the potential to improve healthcare processes and facilitate evidence-based practice. As a means to encourage clinician research engagement and links between speech-language pathology (SLP) clinicians in practice and researchers in higher education institutions, a national SLP clinician-academic research community of practice was established. The first steps for this newly formed research community was to determine stakeholder aims, to prioritize those aims and specify actions which would help respond to the stated priorities. Methods: The study was conducted in Ireland and the Irish Association of Speech and Language Therapists acted as a gatekeeper who forwarded a study information sheet and expression of interest form to its membership. A World Café methodology was utilized to gather data and conducted as part of the inaugural meeting where consent was retrieved. As part of this methodology, the participants created and managed their own data with the help of group facilitators. Results: Thirty six members replied expressing interest and 15 participants attended the inaugural meeting. Participants represented both clinical and research communities and identified and prioritized aims for the research community of practice. The aims were, in order of prioritization: Dissemination, Education, Enablers, Networking and Advocacy. Participants agreed that what they labelled as Dissemination was the number one priority for the newly formed research community of practice. In this context Dissemination referred to the identification of research already being conducted by participants and the sharing of that research both within the group and the larger SLP community nationally and internationally. Various actions were proposed to achieve agreed aims and these reflected a variety of targeted (e.g. development of a research database) and generic (e.g. to act as advocates) activities as well as local and national strategies including lobbying for clinical-research posts. Conclusion: Clear aims, priorities and actions were identified by SLP clinical and research participants to facilitate the development of a research community of practice. This article presents the results of that exercise and outlines the priorities of participants who identified five aims in total. Dissemination was the number one priority for the newly formed research group and manifested a desire to share information about participants' research activities. The prioritized aims reflect assured thinking and form a solid co-constructed footing for the research community to develop and grow.